Game-Based Learning in Chemistry: Development of “Win Redox” Media on Reduction and Oxidation Reactions - Siti Safitriyani; Anisah Tjakrawati (Journal of Chemical Learning Innovation, 2024)
Purpose of the study: This study aims to determine the feasibility of chemistry learning media on the main material of the concept of reduction and oxidation reactions. Methodology: This study uses the Research and Development development method, with the Sugiyono model which includes potential problems, information gathering, product design, design validation, design revision, product trial, product revision, product. Interactive game-based learning media named the win redox game contains material on the concept of reduction and oxidation reactions. The feasibility test of the win redox game is based on the learning outcomes and understanding of Class X students of Madrasah Aliyah Negeri 2 Semarang who have helped in the use of the win redox game and provided feedback on the game. Main Findings: The cognitive learning outcomes of students are included in the moderate category with an increase in learning outcomes (N-gain) of 0.67. The affective aspect learning outcomes of 82.33% are included in the very good category, while the results of student responses of 77.40% are included in the good category, so this interactive game is suitable for use as an alternative learning medium. Novelty/Originality of this study: This study presents "Win Redox" as a game-based learning medium specifically designed to enhance understanding of the concept of redox reactions, a concept rarely developed specifically. Unlike previous research, this medium integrates validated pedagogical design with interactive game elements. This research enriches the existing research by producing a learning medium that is not only engaging but also conceptually feasible and effective.